2015
DOI: 10.1007/s12311-015-0662-z
|View full text |Cite
|
Sign up to set email alerts
|

Inability to Process Negative Emotions in Cerebellar Damage: a Functional Transcranial Doppler Sonographic Study

Abstract: Recent studies have implicated the cerebellum as part of a circuitry that is necessary to modulate higher order and behaviorally relevant information in emotional domains. However, little is known about the relationship between the cerebellum and emotional processing. This study examined cerebellar function specifically in the processing of negative emotions. Transcranial Doppler ultrasonography was performed to detect selective changes in middle cerebral artery flow velocity during emotional stimulation in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This topic has remained controversial [221]. In a study of SCA2 patients [222], Go/NoGo and divided and sustained attention were impaired. These tasks depend on multisensory integration, sequencing, prediction of events, and inhibition of inappropriate responses, all of which are affected by CB damage.…”
Section: Attention In the Ccasmentioning
confidence: 99%
See 1 more Smart Citation
“…This topic has remained controversial [221]. In a study of SCA2 patients [222], Go/NoGo and divided and sustained attention were impaired. These tasks depend on multisensory integration, sequencing, prediction of events, and inhibition of inappropriate responses, all of which are affected by CB damage.…”
Section: Attention In the Ccasmentioning
confidence: 99%
“…Patients with midline lesions demonstrate socialemotional aberrant behaviors [3,12,58,60,263], and social cognition is impaired in CB patients assessed using the "Reading the Mind in the Eyes" test [109]. CB lesions also affect encoding and processing of external negative stimuli [222] and conscious self-monitoring of negative emotion [264].…”
Section: Neuropsychiatry Of the Cerebellum; The Affective Component Omentioning
confidence: 99%
“…The association observed between cerebellar activation in response to angry faces and trait jealousy may also reflect this region’s increasingly recognized role in processing affective stimuli, particularly negative valence ones (Strata, 2015). Indeed, damage to the cerebellum is associated with inability to process negative emotions (Lupo et al, 2015). A case study has also reported delusional behavior in a patient with cerebellar damage (Mitsuhata and Tsukagoshi, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, many scientific studies have recognized the cerebellum as being part of these brain networks (Stoodley and Schmahmann, 2010;Baumann and Mattingley, 2012;Leggio and Olivito, 2018;Clausi et al, 2019a;Van Overwalle et al, 2019a) and have evidenced its role in affective and emotional functioning (Adamaszek et al, 2015;Clausi et al, 2015Clausi et al, , 2019bLupo et al, 2015Lupo et al, , 2018. Accordingly, functional and anatomical connections have been found between the cerebellum and the cortical and subcortical structures involved in both implicit and explicit emotional processing (Critchley et al, 2000;Singer et al, 2004;Schutter et al, 2009;Stoodley and Schmahmann, 2010;Schraa-Tam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%